2017
DOI: 10.1016/j.envres.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the associations of apparent temperature and inflammatory, hemostatic, and lipid markers in a cohort of midlife women

Abstract: Associations between temperature and cardiovascular (CVD) mortality have been reported, but the underlying biological mechanisms remain uncertain. We explored the association between apparent temperature and serum biomarkers for CVD. Using linear mixed effects models, we examined the relationships between residence-proximate apparent temperature (same day and 1, 7, and 30 days prior) and several inflammatory, hemostatic, and lipid biomarkers for midlife women from 1999 through 2004. Our study population consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
(50 reference statements)
0
10
1
Order By: Relevance
“…PM 2.5 also acutely shifted lipoproteins toward a more pro-atherogenic pattern. While both environmental factors are known to affect lipids 5,913,24,25 , this is the first report providing evidence that ambient levels of PM 2.5 and colder outdoor temperatures might each independently impair HDL function. Given the critical role that CEC plays in mitigating the atherosclerotic process 14,15 , our results elucidated a novel mechanistic linkage between PM 2.5 and heightened CV risk 15 .…”
Section: Discussionmentioning
confidence: 75%
“…PM 2.5 also acutely shifted lipoproteins toward a more pro-atherogenic pattern. While both environmental factors are known to affect lipids 5,913,24,25 , this is the first report providing evidence that ambient levels of PM 2.5 and colder outdoor temperatures might each independently impair HDL function. Given the critical role that CEC plays in mitigating the atherosclerotic process 14,15 , our results elucidated a novel mechanistic linkage between PM 2.5 and heightened CV risk 15 .…”
Section: Discussionmentioning
confidence: 75%
“…Cold ambient temperatures have been linked to poor birth outcomes in countries like Sweden (46), but have shown null results in US locations like California (47). One study demonstrated an increased risk for hypertensive disorders during pregnancy (i.e., eclampsia is one of the 21 disorders that comprise a SMM delivery) in the presence of exposure during the preconception period to very cold temperatures for pregnant women in China (22).…”
Section: Discussionmentioning
confidence: 99%
“…Our work parallels other studies highlighting Black compared to White mothers are more susceptible to high ambient temperatures, but prior studies have pointed to increased risk following heat exposure in the third trimester (2). Black women have higher rates of preterm hospitalization after hot temperature exposure in their first and third trimesters in Arizona, Washington, and New York (58) or higher preterm birth among Black birthing populations in the third trimester in Northern California (47). Black women may be more exposed to extreme heat due to their resident locations in areas with less tree canopy and limited access to mitigating measures (e.g., air conditioning) (59).…”
Section: Discussionmentioning
confidence: 99%
“…Royé et al [1,2] indicated that apparent temperature [3] has a strong non-linear relationship with Ischemic Stroke and cardiovascular health. Associations between temperature and cardiovascular mortality have been reported by Basu et al [4], while Alessandrini et al [5] showed a strong relationship between biometeorological conditions and ambulance dispatches in Emilia-Romagna, Italy. Alessandrini et al [5] found that ambulance dispatches increase 1.45% (non-traumatic diseases) and 2.74% (respiratory diseases) for every 1°C increase in the mean apparent temperature between 25° and 30°C.…”
Section: Introductionmentioning
confidence: 89%